PENDIDIKAN DAN PELATIHAN PENGENDALIAN KUTU LONCAT JERUK (Diaphorina citri Kuwayama) SEBAGAI HAMA DAN VEKTOR PENYAKIT CVPD DI DESA TARO, GIANYAR - Wijaya I N.; M. Sritamin; M. Mega Adnyana; W. Adiartayasa; I G. N. Bagus (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2012)
Training on jumping plantlice of citrus (Diaphorina citri Kuw) the vector of CVPD (Citrus Vein Phloem Degeneration) has been held at Taro village, Gianyar regency on 30st July 2012. The activities aimed to know bioecology of D. citri, the vector of CVPD. The training was attended by 32 participants from local farmer groups of Taro village. The method used in activities were lectures, demontration and practical in the citrus field. All participants participited anthusiastically and hope the have the next intensive traning of the citrus culture.